Single sign on environment using UiTM smart card (Barcode) / Noor Hasni Mohd Lehan - Mohd Lehan, Noor Hasni (Faculty of Computer and Mathematical Sciences, 2007)
The users of TMSK website have to repeatedly sign in to use a different application. The user will also need to remember their login id and password. This project will overcome this problem by eliminating the user need to multiple sign in and remembering long password. Instead of typing their login id the user will use the UiTM smart card. The user login identification and password will be recognized using the UiTM smart card barcode where an application will detect them to connect the user to tiie single sign on environment. This project recognized the user using the UiTM smart card barcode. The user information is stored in a database. An application will identify the user identification and password. The user login id and password for the application they requested will be send to the application they requested it exist in the environment.